PENGARUH KOMPENSASI DAN ETOS KERJA TERHADAP KINERJA KARYAWAN PADA KANTOR BERSAMA SAMSAT KARANGASEM - Ni Ketut Cenik Prawaninda; I Wayan Suarjana; Bagus Nyoman Kusuma Putra (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
The success of a company cannot be separated from the improvement of superior and quality human resources. To realize this, human resources really need to be considered, where human resources are one of the most important factors determining the progress of a company. This study aims to determine the effect of compensation and work ethic on employee performance at the Karangasem Samsat Joint Office. This research was conducted at the Karangasem Samsat Joint Office using a population and a sample of 70 respondents. The sampling technique used in this research is the saturated sampling method or the census method. Data was collected through interviews, observations and questionnaires. The data analysis technique used in this study was multiple linear regression analysis which was processed using SPSS version 23.0 software. Based on the results of the analysis of this study, compensation has a positive and significant effect on employee performance at the Karangasem Samsat Joint Office. Work ethic has a positive effect on employee performance at the Karangasem Samsat Joint Office.